Experimental research on plastic deformation of metal foil through ns laser-induced mechanical effects underwater. (February 2021) - Nie, Zeng; Ye, Yunxia; Ren, Yunpeng; Ren, Xudong; Hua, Yinqun; Fu, Yonghong
Highlights: Laser-induced mechanical effects with water as absorbent layer are studied. Three possible mechanisms are responsible for metal foil forming underwater. Different mechanisms are dominant by changing the distance of the focus to foil. Through changing the process parameters, the deformation degree can be changed. Abstract: Laser shock forming (LSF) is an effective method to induce plastic deformation of metal foil, but the need for a solid-state energy absorbent layer during LSF limits its engineering application. Strong shockwave can also be launched by laser-induced breakdown in water because of the nonlinear absorption of water. So through this method, underwater laser-induced mechanical forming (LMF) without specialized absorbent layer can be achieved. In this paper, nanosecond laser was used to induce the breakdown of water. The feasibility of inducing metal foil plastic deformation through LMF with water as the absorbent layer was validated. The surface morphology of the obtained micro pit on the metal foil was observed and measured by a topography measuring instrument and a scanning electron microscope. The laser-induced shockwave and the process of forming bubbles were recorded by a high speed camera. It is found that there are three possible mechanisms responsible for the plastic deformation of metal foil underwater: water-breakdown-induced shockwave, bubble-pulsation-induced shockwave and bubble-collapse-induced micro jet. The dominant forming mechanism and the forming result can be controlled by changing the distance between the laser focus and the foil surface.